Serum and Salivary IgE, IgA, and IgG4 Antibodies to Dermatophagoides pteronyssinus and Its Major Allergens, Der p1 and Der p2, in Allergic and Nonallergic Children - Diego O. Miranda; Deise A. O. Silva; Jorge F. C. Fernandes; Meimei G. J. Queirós; Hamilton F. Chiba; Leandro H. Ynoue; Rafael O. Resende; Janethe D. O. Pena; Sun-Sang J. Sung; Gesmar R. S. Segundo; Ernesto A. Taketomi (Clinical and Developmental Immunology)
Allergic rhinitis (AR) is a public health problem with high prevalence worldwide. We evaluated levels of specific IgE, IgA, and IgG4 antibodies to the Dermatophagoides pteronyssinus (Dpt) house dust mite and to its major allergens (Der p1 and Der p2) in serum and saliva samples from allergic and nonallergic children. A total of 86 children were analyzed, from which 72 had AR and 14 were nonallergic healthy children. Serum IgE and serum/salivary IgG4 levels to Dpt, Der p1, and Der p2 were higher in allergic children whereas serum/salivary IgA levels to all allergens were higher in nonallergic children. IgE levels positively correlated with IgG4 and IgA to all allergens in allergic children, while IgA levels negatively correlated with IgG4 to Dpt and Der p1 in nonallergic children. In conclusion, mite-specific IgA antibodies predominate in the serum and saliva of nonallergic children whereas mite-specific IgE and IgG4 are prevalent in allergic children. The presence of specific IgA appears to have a key role for the healthy immune response to mucosal allergens. Also, specific IgA measurements in serum and/or saliva may be useful for monitoring activation of tolerance-inducing mechanisms during allergen specific immunotherapeutic procedures, especially sublingual immunotherapy.